Harnessing microbiome and probiotic research in sub-Saharan Africa: Recommendations from an African workshop - Reid, G.; Nduti, N.; Sybesma, W.; Kort, R.; Kollmann, T.R.; Adam, R.; Boga, H.; Brown, E.M.; Einerhand, A.; El-Nezami, H.; Gloor, G.B.; Kavere, I.I.; et al. (Springer, 2014)
To augment capacity-building for microbiome and probiotic research in Africa, a workshop was held in Nairobi, Kenya, at which researchers discussed human, animal, insect, and agricultural microbiome and probiotics/prebiotics topics. Five recommendations were made to promote future basic and translational research that benefits Africans.